Intersecting injustices: understanding oppression and privilege through the perspectives of parents facing poverty - Sanfelici, Mara (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2023)
This study contributes to the analysis of intersecting forms of oppression impacting on the daily life of parents facing poverty, valuing their expert knowledge. The research involved forty parents, living in different Italian regions, and known to public or third sector services. Findings highlight how forms of structural, political and epistemic oppression intersect in constructing processes of social vulnerability, which systematically limit the opportunities and initiatives of these parents. The reflections shared by participants also point to possible directions to break out of the “cage of oppression”, affirming different perspectives and discourses that value mutual recognition, reciprocity, while assuming a relational representation of autonomy. Parents’ perspectives are useful to guide the formulation of anti-poverty policies and interventions, oriented by an intersectional lens.